2006
DOI: 10.1007/s10612-006-9012-2
|View full text |Cite
|
Sign up to set email alerts
|

Racialisation in police stop and search practice – the Norwegian case

Abstract: This paper explores the reasons for the conflictual relationship between the police and ethnic minority men in stop and search encounters, which leads to the often heard allegation that ''All police are racists.'' It deals with stop and search practices in Oslo as described in interviews with ethnic minority informants and police officers, and as observed through fieldwork amongst the Oslo police rank and file. The approach is qualitative, and explores the perceptions of those stopped by the police, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
(42 reference statements)
2
32
0
2
Order By: Relevance
“…Sollund's findings, however, are far more ambiguous when it comes to the actual encounters between police and individuals belonging to ethnic minorities and their possible discriminatory nature. Her interviewees from minority backgrounds, confirming the picture from other studies on the subject as well, reported experiences of unfair treatment and even harassment by the police (see also Sollund 2006). At the same time, however, Sollund's own observations of actual police work on the street seemed to qualify this fairly unanimous testimony.…”
Section: Police Culture and Its Dark Side: Verbal Racism As Institutisupporting
confidence: 75%
See 1 more Smart Citation
“…Sollund's findings, however, are far more ambiguous when it comes to the actual encounters between police and individuals belonging to ethnic minorities and their possible discriminatory nature. Her interviewees from minority backgrounds, confirming the picture from other studies on the subject as well, reported experiences of unfair treatment and even harassment by the police (see also Sollund 2006). At the same time, however, Sollund's own observations of actual police work on the street seemed to qualify this fairly unanimous testimony.…”
Section: Police Culture and Its Dark Side: Verbal Racism As Institutisupporting
confidence: 75%
“…Holmberg 2000, Sarnecki 2006, Sollund 2006. Rather, the purpose of this article has been to consider whether the police's verbal racism, joking culture, and language use within the organisation might present themselves as a potential problem regardless of whether, and how, they might influence police officers' professional conduct towards ethnic minorities outside the organisation.…”
Section: Discussion and Conclusion: Cracking The Diversity Bubblementioning
confidence: 99%
“…They were all subjected to crimes by people that they identified as 'Swedes'. Research has shown that young people with an immigrant background are especially likely to be targeted by the police (Fassin 2013;Neild 2009;Sollund 2006) and that researchers use discrimination when accounting for distrust that may lead to refraining from reporting crimes (Pettersson 2014). With this in mind, we expected that our interviewees would draw on such experiences and that we would hear stories about unfair police treatment because they had an immigrant background.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the police and young people with an immigrant background are well researched internationally and are often discussed in the context of discrimination (Brunson 2007;Fassin 2013;Sollund 2006). The relationships of police and young people with an immigrant background living in a socially underprivileged area illustrate how young people perceive ethnic discrimination to be an issue in these interactions (Pettersson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This means that an approach which involved endeavouring to avoid having any influence and to stay completely out of the way might, paradoxically, also result in worse data, i.e. in observations that provide less information about the situations of interest and the work of the police (Emerson, Fretz, & Shaw, 2011;Holmberg, 2003;Sollund, 2006).…”
Section: The Studymentioning
confidence: 99%